Seroprevalence of severe fever with thrombocytopenia syndrome virus in China: A systematic review and meta-analysis. - Peng Li; Zhen-Dong Tong; Ke-Feng Li; An Tang; Ya-Xin Dai; Jian-Bo Yan (PLoS ONE, 2017)
Objective Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus-SFTSV. The seroprevalence of anti-SFTSV antibodies including immunoglobulin G (IgG) and immunoglobulin M (IgM), specific to SFTSV in the general population has been investigated in various epidemiological studies with inconsistent results. Here, we clarify this discrepancy and reach a more comprehensive result by mean of a meta-analysis. Methods All relevant articles were searched in the electronic databases (PubMed, Web of science, Embase, Chinese National Knowledge Infrastructure database, Chinese Wanfang database) up to November 2016. The pooled seroprevalence and 95% confidence intervals (95% CIs) were calculated by random- or fixed- model on the basis of heterogeneity. Results In total, 21 studies containing 23,848 blood samples from 7 provinces were included in this meta-analysis. The minimum and maximum reported seroprevalences of SFTSV among humans in China were 0.23% and 9.17%, respectively. The overall pooled seroprevalence of SFTSV antibodies was 4.3% (95%CI: 3.2%-5.5%). The pooled prevalence was 5.9% (95%CI: 4.7%-7.0%) in Zhejiang province, 4.9% (95%CI: 4.1-5.8%) in Anhui province, 3.9% (95%CI: 1.3%-6.4%) in Shandong province, and 0.7% (95%CI: 0.2%-1.1%) in Jiangsu province. Stratified by occupation, the pooled prevalence of farmer was 6.1% (95%CI: 3.4%-8.9%) and others (mainly are students) was 3.3% (95%CI: 2.4%-4.2%). Additionally, seroprevalence of SFTSV in people who lived in the same village with the patient were higher than that of people who lived in a different village. Seropositive rates in sampling years after 2012 were higher than that before 2012. The prevalence of SFTSV did not differ by age or gender. Sensitive analysis by omitting one study at a time indicated the results of the pooled seroprevalence were robust. Conclusions Seroprevalence of SFTSV among healthy population in central and eastern China is high. Surveillance efforts on mild or asymptomatic infections among endemic persons are needed.